Role of Microbiota in Pathogenesis and Management of Viral Hepatitis - Sehgal, Rashi; Bedi, Onkar; Trehanpati, Nirupma (Frontiers in Cellular and Infection Microbiology, 2020)
Hepatitis is a condition which can be self-limiting or can progress to fibrosis (scarring), cirrhosis or liver cancer. These days, gut microbiota becomes an important part of our immune system which is important for disease progression or recovery. Translocation of gut microbial and metabolic products causes intestinal inflammation by modulating immune cells leading to impairment of primary barrier. But there are limited studies discussing pathogenesis and management of hepatitis with gut microbiota. In this review, we have discussed the role of gut microbiota in pathogenesis and management of various hepatitis especially Hepatitis B and C. We have discussed the role of bacterial products, LPS-TLR4 pathway, un-methylated CpG DNA which ultimately affects downstream NF-kB signaling in hepatitis. Finally, we have discussed the role of fecal microbiota transplantation in the management of hepatitis.